1982
DOI: 10.1016/0005-2760(82)90246-6
|View full text |Cite
|
Sign up to set email alerts
|

Localization of glycerophosphate acyltransferase in Escherichia coli

Abstract: sn-Glycero-3-phosphate acyltransferase (EC 2.3.1.15) the first enzyme involved in phospholipid biosynthesis, is known to be associated with the cytoplasmic membrane of Escherichiu cofi. The localization of this enzyme in the transverse plane of the membrane was investigated by proteolysis of intact and lysed spheroplasts and by inhibition of glycerol 3-phosphate transport into intact cells in the presence of azide. Glycerophosphate acyltransferase was found to be resistent to proteolysis by trypsin in intact s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We have previously shown that in this membrane [7] as well as in reconstituted model membranes [5] all active sites of the glycerophosphate acyltransferase are present at one side of the membrane. The latency of the enzyme in E. coli spheroplasts [7] indicates absence of acylation when both substrates are present at the side of the membrane opposite to the active site. Here we investigate whether the glycerophosphate acyltransferase can function properly when each of the substrates is present at a different side of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that in this membrane [7] as well as in reconstituted model membranes [5] all active sites of the glycerophosphate acyltransferase are present at one side of the membrane. The latency of the enzyme in E. coli spheroplasts [7] indicates absence of acylation when both substrates are present at the side of the membrane opposite to the active site. Here we investigate whether the glycerophosphate acyltransferase can function properly when each of the substrates is present at a different side of the membrane.…”
Section: Resultsmentioning
confidence: 99%